Answer:
d = -1/3, 0
Step-by-step explanation:
Subtract the constant on the left, take the square root, and solve from there.
(6d +1)^2 + 12 = 13 . . . . given
(6d +1)^2 = 1 . . . . . . . . . .subtract 12
6d +1 = ±√1 . . . . . . . . . . take the square root
6d = -1 ±1 . . . . . . . . . . . .subtract 1
d = (-1 ±1)/6 . . . . . . . . . . divide by 6
d = -1/3, 0
_____
Using a graphing calculator, it is often convenient to write the function so the solutions are at x-intercepts. Here, we can do that by subtracting 13 from both sides:
f(x) = (6x+1)^ +12 -13
We want to solve this for f(x)=0. The solutions are -1/3 and 0, as above.
The expression 256 + 4 is equivalent to (200 + 4) + (40+4) + (16+4) according to distributive and commutative property of addition.
Given the expression 256 + 4. This can be solved using the partial sum expressed as:
256 + 4
256 + 4
= (200 + 40 + 16) + 4
According to the commutative property, A+B = B+A
The arrangement does not affect the result. Hence;
- (200 + 40 + 16) + 4 = 4 + (200 + 40 + 16)
Using the distributive law;
- 4 +(200 + 40 + 16) = (200 + 4) + (40 + 4) + (16 + 4)
Hence the expression 256 + 4 is equivalent to (200 + 4) + (40+4) + (16+4) according to distributive and commutative property of addition.
Learn more on partial sum here: brainly.com/question/6958503
Answer:its the Third option C
Step-by-step explanation:
Because if u divide 3 by 4 you get .75 which is out of 100 %